EPIDEMIOLOGICAL FEATURES OF VIRAL HEPATITIS A DISSEMINATION AMONG CHILDREN IN THE ANDIJAN REGION AND OPTIMIZATION OF PREVENTIVE STRATEGIES (International journal of medical sciences, 2025)
Objective: To analyze the epidemiological trends of Viral Hepatitis A (HAV) among children in the Andijan region over a 5-year period (2019-2023) and to evaluate the effectiveness of current preventive measures in order to propose an optimized control strategy. Methods: A retrospective descriptive epidemiological study was conducted using official statistical data from the Andijan Regional Service for Sanitary-Epidemiological Welfare and Public Health (SES). The study population included all reported cases of HAV in children aged 0-14 years. We analyzed incidence rates per 100,000 population, age-specific distribution, seasonality, and potential transmission routes. Additionally, a case-control survey of 200 households (100 with a recent HAV case, 100 controls) was performed to identify risk factors related to water supply and hygiene practices. Results: The average annual incidence of HAV in children was 345.2 per 100,000, significantly higher than the national average. A clear seasonal pattern was observed, with 72% of cases occurring between September and December (autumn peak). The age distribution showed a shift: while children aged 3-6 years accounted for 45% of cases, a rising trend (30% increase) was noted in the school-age group (7-14 years). The case-control analysis revealed that consumption of unboiled tap/open-source water (OR=3.8) and lack of indoor plumbing (OR=2.5) were primary risk factors. Vaccination coverage in the target group (18 months) was 92%, yet "breakthrough" outbreaks occurred in unvaccinated older cohorts. Conclusion: Andijan region remains an area of intermediate-to-high endemicity for HAV, driven by water safety challenges and high population density. The current vaccination strategy, focused solely on toddlers, leaves a susceptibility gap in school-aged children. Optimization strategies must include: 1) Catch-up vaccination for children aged 7-10 years; 2) Targeted "WASH" (Water, Sanitation, Hygiene) interventions in schools during the pre-epidemic period (August); and 3) Stricter control of water safety in rural districts.